Indonesia in BRICS: A Realist Perspective - Lee, Brice Tseen Fu; Kornphetcharat, Kotchaphop; Sims, Juan Pablo (UI Scholars Hub, 2025)
Indonesia’s 2025 accession to BRICS (Brazil, Russia, India, China, and South Africa) appears at odds with the country’s long-standing bebas-aktif (“free and active”) tradition of non-alignment. This article explains the move through a layered realist approach and a purely theoretical, deductive method. First, the study integrates structural, offensive, and neoclassical realism to clarify four key mechanisms external balancing, hedging, relative gains, and status-seeking. It then maps propositions about what BRICS can offer Indonesia and tests them against existing realist scholarship on middle powers and emerging-power clubs. Analysis shows that BRICS chiefly serves as an external-balancing instrument, reducing Jakarta’s reliance on Western-centric institutions. Although any state can purchase shares in the New Development Bank (NDB), full BRICS membership ensures larger voting power over lending policy, enhancing Indonesia’s leverage while still granting access to faster, less conditional finance. Intra-BRICS technology partnerships and China-led Belt and Road projects promise additional relative gains, reinforcing economic and strategic autonomy. At home, membership boosts symbolic status, validating elite ambitions and a developmental-nationalist narrative. Yet Jakarta’s engagement remains deliberately shallow: it taps BRICS where pay-offs are high and keeps exit options open to avoid over-dependence on any single great power. The findings confirm core realist expectations: middle powers exploit an increasingly diversified institutional landscape to hedge against post-unipolar uncertainty and to bargain for better terms. Influence in today’s system accrues to actors that supply flexible, mutually reinforcing institutional choices rather than rigid blocs.